Tracking spin-axis orbital alignment in selected binary systems: the Torun Rossiter–McLaughlin effect survey. Issue 2 (12th June 2018) - Sybilski, P; Pawłaszek, R K; Sybilska, A; Konacki, M; Hełminiak, K G; Kozłowski, S K; Ratajczak, M
ABSTRACT: We have obtained high-resolution spectra of four eclipsing binary systems (FM Leo, NN Del, V963 Cen and AI Phe) with the view to gaining an insight into the relative orientations of their stellar spin axes and orbital axes. The so-called Rossiter–McLaughlin (RM) effect, i.e. the fact that the broadening and the amount of blue or redshift in the spectra during an eclipse depends on the tilt of the spin axis of the background star, has the potential of reconciling observations and theoretical models if such a tilt is found. We analyse the RM effect by disentangling the spectra, removing the front component and measuring the remaining, distorted lines with a broadening function (BF) obtained from single-value decomposition (SVD), weighting by the intensity centre of the BF in the eclipse. All but one of our objects show no significant misalignment, suggesting that aligned systems are dominant. We provide stellar as well as orbital parameters for our systems. With five measured spin-orbit angles, we increase significantly (from 9 to 14) the number of stars for which it has been measured. The spin-orbit angle β calculated for AI Phe's secondary component shows a misalignment of 87±17°. NN Del, with a large separation of components and a long dynamical time-scale for circularization and synchronization, is an example of a close to primordial spin-orbit angle measurement.